Civil 'jurisdiction' of Syariah Court in Malaysia - should it be expressed or implied?: a reflection - Md. Dahlan, Nuarrual Hilal; Kamarudin, Abdul Rani (2005)
The jurisdiction of Syariah Courts to hear matters its own matters is generally provided and fallen under List II (State List) of the 9th Schedule to the Federal Constitution ('FC') and spesifically provided in the respective states' enactments on the administration of Islamic Law enactments and for the Federal Territories an act passed by Parliament. However, there are certain matters that have been left by the legislatures to have them being spesifically provided in the said provisions even though it involves the determination of Islamic Law as enrished in List II (State List) under the Ninth Schedule to the FC. In such situation, what is the position of Syariah Court? Could it determine the matters even though it had not been provided by the legislature? This paper will highlight these issues through cases decided in courts in Malaysia.